2013
DOI: 10.1521/soco.2013.31.5.578
|View full text |Cite
|
Sign up to set email alerts
|

Reading Narrative Fiction Reduces Arab-Muslim Prejudice and Offers a Safe Haven From Intergroup Anxiety

Abstract: Inquiry into the written narrative's effect on social cognition is normally left to literary scholars and philosophers. Two experiments demonstrated narrative fiction's power to elicit empathy and reduce implicit and explicit prejudice against Arab-Muslims. Participants were randomly assigned to read a full narrative, condensed narrative, or a non-narrative. critically, the full and condensed narratives were matched on counterstereotypical exemplars and exposure to Arab-Muslim culture so that the additional re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 58 publications
2
72
0
Order By: Relevance
“…Related to this point, we note that we did not control for the effects of reading other fictional books where positive and negative characters can be easily identified. However, we controlled for general book reading because education in general (e.g., Bilali & Vollhardt, ) and book reading in particular (Johnson, Huffman, & Jasper, ; Johnson, Jasper, Griffin, & Huffman, ; Vezzali et al., ) have been shown to be associated with reduced prejudice. Although this research focused on Harry Potter books as they are representative of fiction literature with large‐scale appeal to the public, similar research can focus on other popular published fictional books.…”
Section: Discussionmentioning
confidence: 99%
“…Related to this point, we note that we did not control for the effects of reading other fictional books where positive and negative characters can be easily identified. However, we controlled for general book reading because education in general (e.g., Bilali & Vollhardt, ) and book reading in particular (Johnson, Huffman, & Jasper, ; Johnson, Jasper, Griffin, & Huffman, ; Vezzali et al., ) have been shown to be associated with reduced prejudice. Although this research focused on Harry Potter books as they are representative of fiction literature with large‐scale appeal to the public, similar research can focus on other popular published fictional books.…”
Section: Discussionmentioning
confidence: 99%
“…The role of perspective taking in changing social attitudes may also explain findings that fiction about the experiences of members of other groups can lead to increased empathy and positive attitudes towards those groups (Bilali & Vollhardt, 2013;Hakemulder, 2000Hakemulder, , 2008Johnson, Jasper, Griffin, & Huffman, 2013;Paluck, 2007;Vezzali, Stathi, Giovannini, Capozza, & Trifiletti, 2015). Several researchers have suggested that fiction has a functional role as a form of technology which allows us to experience the world through the eyes of others and thus allows us to identify more closely with them blurring the boundary between self and other (Koopman & Hakemulder, 2015;Mar & Oatley, 2008;Oatley, 2016).…”
Section: Perspective Takingmentioning
confidence: 99%
“…For instance, radio dramas effectively communicate new social norms (Paluck, ), which in turn influence behaviour (Cialdini & Trost, ). In addition, fictional narratives expose listeners to diverse opinions in non‐threatening ways, thereby reducing intergroup anxiety (Johnson, Jasper, Griffin, & Huffman, ) and encouraging perspective taking with characters from different sides of the conflict (Paluck, ). These processes can reduce out‐group prejudice in the context of the actual conflict (Bilali & Vollhardt, ).…”
mentioning
confidence: 99%